Microbiological analysis and pesticides in tomatos consumed in Botucatu-SP, Brazil - Diniz de Castro, Renata Saad [UNESP]; Daiuto, Erica Regina [UNESP]; Vieites, Rogerio Lopes [UNESP] (Univ Federal Mato Grosso, 2016)
The objective of this study was to evaluate the tomato quality, as for the chemical and microbiological dangers, consumed at some restaurants of Botucatu-SP city. The samples tomato were obtained of 10 restaurants, selected randomly, and under previous authorization. The tomatoes were appraised as for the chemical dangers, being accomplished analysis of the main pesticides used in the culture. As for the microbiological risks in the tomatoes the determination of the Most probable Number was accomplished (NMP) of total coliformes (CTo) and termotolerantes (CTe). The collected tomatoes were not in accordance with the patterns of the effective legislation for total coliformes. The collected tomatoes presented superior concentrations to the limits allowed for the pesticides imidacloprid and chlorpyrifos in several establishments. The Good Agricultural Practices should be associated to the Good Practices of Production for the supply of safe tomatoes to the human consumption.
Keywords: pesticides; residues; microbiological risc